A qualitative study of risk perception and preparedness knowledge in two Midwestern United States communities that are located near nuclear power plants. Issue 2 (13th January 2021) - Crowley, Julia
Abstract: The purpose of this research is to examine risk perceptions of communities living near nuclear power plants and to relate the risk perceptions to the local knowledge of preparedness procedures in the event of an accident at the facilities. A total of 65 interviews were conducted in 2 communities in a Midwestern state in the United States that has nuclear power plants. Questions pertained to risk perceptions and knowledge of preparedness procedures in regards to the nuclear power plants. Interview transcripts were coded through the two‐step process of initial and focused coding to derive four themes. These themes include quality of life, energy production, safety, and preparedness knowledge. The majority of interviewees reported that the facilities enhanced their quality of life with the taxes paid by the parent company. In addition, most interviewees described the energy production process as clean. While most of the interviewee safety perceptions were positive overall, some expressed concerns regarding the potential for an accident at one of the nuclear power plants. In regards to preparedness knowledge, fewer than half of interviewees could name at least one preparedness procedure offhand. This research concludes that interviewees with low‐risk perceptions of the facilities were less prepared overall.